Analysis of Five Earthy-Musty Odorants in Environmental Water by HS-SPME/GC-MS - Zhen Ding; Shifu Peng; Weiwen Xia; Hao Zheng; Xiaodong Chen; Lihong Yin (International Journal of Analytical Chemistry)
The pressing issue of earthy and musty odor compounds in natural waters, which can affect the organoleptic properties of drinking water, makes it a public health concern. A simple and sensitive method for simultaneous analysis of five odorants in environmental water was developed by headspace solid-phase microextraction (HS-SPME) coupled to chromatography-mass spectrometry (GC-MS), including geosmin (GSM) and 2-methylisoborneol (2-MIB), as well as dimethyl trisulfide (DMTS), β-cyclocitral, and β-ionone. Based on the simple modification of original magnetic stirrer purchased from CORNING (USA), the five target compounds can be separated within 23 min, and the calibration curves show good linearity with a correlation coefficient above 0.999 (levels = 5). The limits of detection (LOD) are all below 1.3 ng L−1, and the relative standard deviation (%RSD) is between 4.4% and 9.9% (n = 7) and recoveries of the analytes from water samples are between 86.2% and 112.3%. In addition, the storage time experiment indicated that the concentrations did not change significantly for GSM and 2-MIB if they were stored in canonical environment. In conclusion, the method in this study could be applied for monitoring these five odorants in natural waters.